(untitled) (American Journal of Islam and Society, 2007)
Perceptions of the “other” are a powerful force in day-to-day human interaction, as well as in domestic and international politics. Since the publication of Edward Said’s Orientalism almost three decades ago, many scholars have appropriated and debated his thesis about the reality-changing power of European (and American) discourses on Muslims and Arabs. In the book under review, Timothy Marr, professor of English in the American Studies Curriculum department at the University of North Carolina, Chapel Hill, simultaneously broadens and criticizes Said’s ideas. The Cultural Roots of American Islamicism (a somewhat misleading title for a fascinating book) offers a rich analysis of how Americans appropriated images of Islam, Muslim societies, and the Middle East during the seventeenth to nineteenth centuries for various political, social, and cultural – but ultimately American – purposes related to domestic and international issues. The author argues that such perceptions, in light of their complex and multiple uses in American history, are significant because they continue to shape contemporary American approaches to the Muslim world. Marr advances this thesis by looking at an impressive array of historical sources and documents, as well as secondary literature on various aspects of American history and culture, in which he finds a multitude of references to Islam and Muslims (or Turks, Saracens etc., respectively). His analysis of these references offers a stunning kaleidoscope of American images of the Muslim “other,” but reveals far more about the inner dynamics of American nation-building and cultural self-definition than about Islam or Muslims ...